The influence of coconut fibres and ground steel slag on strength and durability properties of recycled aggregate concrete: sustainable design of fibre reinforced concrete - Thamer Alomayri; Ahmed M. Yosri; Babar Ali; Syed Safdar Raza; Muhammad Yaqub; Rawaz Kurda; Ahmed Farouk Deifalla (Journal of Materials Research and Technology, 2023)
This research work proposed an economic and eco-efficient idea to supplement the ductility and durability of concrete by the simultaneous incorporation of several processed waste materials i.e., ground blast furnace slag (GBFS), recycled coarse aggregate (RCA), and coconut fibre (CF). Two concrete families were produced containing 0% and 100% coarse RCA. GBFS was incorporated as by 25% replacement for cement. CF was used as a fibre reinforcement at 0.25% volume fraction. The results revealed that the recycled-aggregate concrete (RAC) modified with GBFS, CF, and modified plasticizer dosage can attain similar or higher mechanical performance than unmodified natural-aggregate concrete (NAC). At a later age, the strength gain in RAC mixes due to 25% GBFS addition was found to be notably greater than that observed in NAC mixes. At 91 days, RAC containing 0.25% CF and 25% GBFS correspondingly showed 30.5% and 33% more flexural strength and splitting tensile strength, as compared to conventional plain NAC. GBFS inclusion can effectively eliminate the corrosion risk of medium-strength NAC and RAC and control the negative effects of CF incorporation on the durability of concrete. RAC with 0.25% CF and 25% GBFS yielded 1.5% and 16% lower water absorption than plain NAC, at 28 and 91 days, respectively. The modification of SP dosage can substantially enhance the strength and permeability-resistance of CF-reinforced RAC.